Inhibition of cellular proliferation and enhancement of hydrogen peroxide production in fibrosarcoma cell line by weak radio frequency magnetic fields - Castello, Pablo Raul (2014)
This study presents experimental data for the effects of weak radio frequency (RF) magnetic fields on hydrogen peroxide (H2O2) production and cellular growth rates of fibrosarcoma HT1080 cells in vitro. Cells were exposed either to 45μT static magnetic fields (SMFs)-oriented vertical to the plane of growth or to SMFs combined with weak 5 and 10MHz RF magnetic fields of 10μTRMS intensity perpendicular to the static field. Cell numbers were reduced up to 30% on Day 2 for the cells exposed to the combination of SMF and a 10MHz RF magnetic field compared with the SMF control cells. In addition, cells exposed to 10MHz RF magnetic fields for 8h increased H2O2 production by 55%. The results demonstrate an overall magnetic field-induced biological effect that shows elevated H2O2 levels with accompanying decrease in cellular growth rates.